Implementation of Occupational Safety and Health Programs on the Worker Behavior in the Construction of Bocimi Toll Road Section II - Mitsaq Addina Nisa; Danang Purwanto; M. Tegar S.A (LEADER: Civil Engineering and Architecture Journal, 2023)
One of the reasons is that road construction in Indonesia is increasing every year. In the construction of toll roads, this activity absorbs more and more workers increase. Besides that, this activity carries the risk of work accidents, by because that is why the safety and health aspects of work K3 must always be important applied in these activities. This research was conducted to find out. Does the occupational safety and health program have an influence on unsafe behavior of workers during the construction of the Bocimi toll road section II. This method uses multiple regression with a cross-sectional approach to see how much influence the independent variable has on the dependent variable. There were 100 respondents in this study, each respondent was given as many as 20 statements using a Likert scale. Based on the results Data processing shows that the influence of safety work program factors and occupational health on workers' unsafe behavior factors obtained t count = -2.283 > t table = -1.984 and calculated f = 5.211 > 3.944. This shows that the influence of occupational safety and health work program factors on unsafe worker behavior. Meanwhile, the relationship between work program factors occupational safety and health with factors of worker unsafe behavior obtained p = 0.025. This shows H1 (there is influence) and the relationship between occupational safety and health work program factors on unsafe behavior worker.